The GIIPS crisis in the context of the European Monetary Union: a political economy approach - Blikstad, Nicholas Magnus Deleuse; Oliveira, Giuliano Contento de (Brazilian Keynesian Review, 2019)
The GIIPS crisis (Greece, Italy, Ireland, Portugal, and Spain) has been deep and resistant. To date there have not been clear signs of consistent recovery from these economies, with the only exception being Ireland, that has experimented with a longer lasting economic recovery process in recent times. The aim of this paper is to discuss the GIIPS crisis in light of the European integration project. It is argued that this crisis has resulted from two simultaneous processes: on the one hand, it has resulted from the growing internal imbalances that occurred over the economic expansion period; on the other hand, it has resulted from the rigidities imposed by the institutional arrangement of the European Monetary Union. It has been concluded that the consistent economic recovery of these economies requires an aggregate demand stimulus for them, a condition that in turn requires the implementation of countercyclical economic policies.